Antibiotics From Microbes: Converging To Kill - Fischbach, Michael A. (2009)
As genetically encoded small molecules, antibiotics are phenotypes that have resulted from mutation and natural selection. Advances in genetics, biochemistry, and bioinformatics have connected hundreds of antibiotics to the gene clusters that encode them, allowing these molecules to be analyzed using the tools of evolutionary biology. This review surveys examples of convergent evolution from microbially produced antibiotics, including the convergence of distinct gene clusters on similar phenotypes and the merger of distinct gene clusters into a single functional unit. Examining antibiotics through an evolutionary lens highlights the versatility of biosynthetic pathways, reveals lessons for combating antibiotic resistance, and provides an entry point for studying the natural roles of these natural products.